Implementasi Tata Kelola Teknologi Informasi Berdasarkan Framework COBIT 5 Pada PT Krakatau Tirta Industri - Safira Widya Hapsari; Ismiarta Aknuranda; Retno Indah Rokhmawati (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Information technology was expanding rapidly and widely spread in all sectors of the field. One of the points in the Regulation of the Ministry of State Owned Enterprises Number: PER-02/MBU/2013 About the Information Technology Management Preparation Guidelines of State Owned Enterprises explained that the utilization and development of information technology in SOEs should be based on a governance system. PT Krakatau Tirta Industri was a SOE that had not implemented a framework in managing their information technology governance. This study aimed to find out the implementation results of COBIT 5 framework on companies in managing information technology governance. The implementation process adapted COBIT 5 implementation life cycle and was only done until the design phase. The phases were identificating the need to change; mapping the enterprise goals, IT-related goals and IT processes; analysing the current capability levels; analysing the target capability level; analysing the gap and composing improvement recommendations. Based on current domain DSS04 capability level assessment, PT Krakatau Tirta Industri was at level 1 and had a gap of 2 as the company set the target capability level at level 3. The end result of this study was the design of improvement recommendations of base practice procedures and output documents that were not available yet to meet level 1.